Athens and Rome Contrasted: The Present Challenge of Managing Two Manners of Classicism - Loukaki, Argyro (Actual Problems of Theory and History of Art, 2020)
The main contribution of the present article is the original comparison of the archetypal yet different classicisms of Athens and Rome, with emphasis on the physical, metaphysical, aesthetic and moral aspects of the management of their central archaeological loci. Athens and Rome are the two preeminent classical cities globally. Their world heritage has been nurturing for centuries global collective memory, creativity, inspiration, and myth. The Sacred Rock of the Athenian Acropolis is the epitome of democracy, classical beauty and urban constitution; the Acropolis spatialities are a form of vital energy. The Roman Forum, alongside the neighboring Colosseum, joins and represents imperial power, structural prowess and prominent urbanism. Enduring through tests of time, iconic classical ruins stage modern urban action, real and symbolic.They recapitulate cities as syntactic urban permanences, trigger new creativity, and loom in struggles over nationaland global representation — indicatively, following the “fever for marble,” classical ruins involuntarilysupplied museum collections with architectural members and statues —, plus artistic relevance and progress. With regard to the planning–preservation interface, major archaeological urban landscapes like the Acropolis and the Forum–Colosseum pair are usually involved in six distinct processes. First, their unearthing usually demands planned excavation expeditions. Second, subject to various preservation regulations, the new development around them may be completely stopped or highly controlled with the effect that urban density is drastically lowered. Third, they may undergo restoration, a demanding and time-consuming process which radically alters their public presence. Fourth, they may be accompanied by museums specifically built in their vicinity, like it happens in this case with the New Acropolis Museum. Fifth, they are usually linked to the surrounding urban space, and sometimes to other archaeological sites, via landscaped gardens and pedestrian zones functioning as transitional areas or corridors. Sixth, they may necessitate protection from environmental pollution, infrastructural works or other sources of deterioration. The points addressed by the article are the prosaic and sublime aspects of classicism(s) plus similarities and differences between Athens and Rome. Their archaeological cores inspire creative imagination in architectural, artistic, aesthetic and literary terms. More specifically, in this article are discussed: the Greek archaeological context in conjunction with a number of important issues; the Italian archaeological and political context before and after Fascism, in parallel with the Roman past and ruins; the formation of the Athenian archaeological landscape in the 1950s as a major accomplishment of architect Dimitris Pikionis; the present Roman archaeological landscape, compared with Pikionis’. Further, aesthetic notions like the urban uncanny and urban lightness/luminosity are substantiated around Roman and Athenian classicism respectively.